The Development of a Covid - 19 Surveillance with Network Participation Model for Thai People in State Quarantine after Returning by Land at the Thai-Malaysian Border: Kittiporn Nawsuwan - Baitayeb, Kornurai; Nawsuwan, Kittiporn; Singweratham, Noppcha; BoonSrichan, Bungorn (Princess of Naradhiwas University Journal, 2024)
This research and development aimed to: 1) study the operational situation and participation in Covid-19 Surveillance networks, 2) develop a network participatory model for Covid-19 surveillance and state quarantine, 3) study the effectiveness of the model. The study was conducted between February 2021 and January 2022, including 4 steps as follows. Step 1 was the situation analysis on the operating situation and participation of the networks. Step 2 was the model development. Step 3 was the model experimentation so to study its effectiveness. The sample was 45 participants from networks. Step 4 was a study of the key success factors of the operation from the networks. Quantitative data and qualitative data were collected. The data were analyzed by descriptive statistics, one-sample t-test, and content analysis. The results showed as follows. 1. The participation of the networks in Covid-19 surveillance in Sadao District of Songkhla Province was at a low level in all aspects. The participation of network partners model in State Quarantine was SADAO Care Model, consisting of 1) Strategy 2) Solidarity) 3) Association4) Assignment 5) Doing 6) Development 7) Assessment 8) Allocation and Benefits 9) Our Best Teamwork and 10) Overcoming Power of Unity. 3. After using the model, an overall mean score of the participation was more than 3.50, with statistical significance at the .001 level. 4. The top three key success factors were providing friendly and caring service, effective coordination of agencies in all sectors as well as the readiness of medical personnel and hotel employees. The model should be used to set policies, strategies, and action plans for other Covid-19 surveillance and control in the next wave or other emerging diseases, so to strengthen the organization and surveillance networks.